Aramaean borders
1 online resource.
Keywords: This book is devoted to the analysis of borders of the Aramaean polities and territories during the 10th–8th centuries B.C.E. Specialists dealing with various types of documents (Neo-Assyrian, Aramaic, Phoenician, Neo-Hittite and Hebrew texts), invited by Jan Dušek and Jana Mynářová, addressed the topic of the borders of the Aramaean territories in the context of the history of three geographical areas during the first three centuries of the 1st millennium B.C.E.: northern Mesopotamia and the Assyrian space, northern Levant, and southern Levant. The book is particularly relevant to those interested in the history and historical geography of the Levant during the Iron Age.